2022
DOI: 10.1101/2022.08.24.504986
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distinct Nrf2 Signaling Thresholds Mediate Lung Tumor Initiation and Progression

Abstract: Mutations in the KEAP1-NRF2 pathway occur in up to a third of non-small cell lung cancer (NSCLC) cases and often confer resistance to therapy and poor outcomes. Here, we developed murine alleles of the KEAP1 and NRF2 mutations found in human NSCLC and comprehensively interrogated their impact on tumor initiation and progression. Chronic Nrf2 stabilization by Keap1 or Nrf2 mutation was not sufficient to induce tumorigenesis, even in the absence of tumor suppressors p53 or Lkb1. When combined with KrasG12D/+, co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 69 publications
2
7
0
Order By: Relevance
“…Mice were infected intranasally with 2×10 7 PFU adenovirus (Ad5CMVCre, University of Iowa) under isofluorane anesthesia to initiate tumor development. Mice developed tumors with a median survival of approximately 4 months post infection as previously reported (DeBlasi et al ., 2022; Jackson et al, 2005), and mice were used for experiments between 3-3.5 months when they displayed evidence of tumor burden such as rapid respiration. To generate experimental animals with SCLC tumors, Rb1 flox/flox ; Trp53 flox/flox ; Myc LSL/LSL mice were intercrossed to generate Rb1 flox/flox ; Trp53 flox/flox ; Myc LSL/+ (RPM) and Rb1 flox/flox ; Trp53 flox/flox ; Myc LSL/LSL (RPMM) experimental animals (Mollaoglu et al, 2017).…”
Section: Methodssupporting
confidence: 61%
See 2 more Smart Citations
“…Mice were infected intranasally with 2×10 7 PFU adenovirus (Ad5CMVCre, University of Iowa) under isofluorane anesthesia to initiate tumor development. Mice developed tumors with a median survival of approximately 4 months post infection as previously reported (DeBlasi et al ., 2022; Jackson et al, 2005), and mice were used for experiments between 3-3.5 months when they displayed evidence of tumor burden such as rapid respiration. To generate experimental animals with SCLC tumors, Rb1 flox/flox ; Trp53 flox/flox ; Myc LSL/LSL mice were intercrossed to generate Rb1 flox/flox ; Trp53 flox/flox ; Myc LSL/+ (RPM) and Rb1 flox/flox ; Trp53 flox/flox ; Myc LSL/LSL (RPMM) experimental animals (Mollaoglu et al, 2017).…”
Section: Methodssupporting
confidence: 61%
“…While we previously reported that Nrf2 promoted CDO1 accumulation in a Keap1 R554Q model of LUAD (Kang et al ., 2019), this analysis was on the low-grade tumors that are most frequent in the Keap1 R554Q model. The Nrf2 D29H tumors of sufficient size for excision for metabolomics analysis in this study were instead higher-grade adenocarcinomas that we find downregulate Nrf2 and target protein expression (DeBlasi et al, 2022), which will influence CDO1 stabilization. We previously reported that the downregulation of taurine synthesis conserves both cysteine and NADPH (Kang et al ., 2019), but taurine is still a requirement due to its role in osmolarity control, mitochondrial translation, redox regulation, and other processes (Ward and DeNicola, 2019).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…However, we saw no change in survival with G6PD-deficiency in KPC mice, pointing to clear differences in NADPH and ROS control in precancerous lesions compared to advanced disease. A similar, yet distinct, phenomena has been described with the KEAP1/NRF2 pathway in lung tumorigenesis, where NRF2 activation (by Keap1 deletion) promotes oncogenic Kras -induced tumor initiation but impairs tumor progression 53 .…”
Section: Discussionsupporting
confidence: 53%
“…LSL-Kras G12D/+ ; p53 flox/flox ; Nrf2 D29H/+ mice were described previously 28 . Mice were housed and bred in accordance with the ethical regulations and approval of the University of South Florida Institutional Animal Care and Use Committee (protocol numbers: IS00005814M and IS00003893R).…”
Section: Methodsmentioning
confidence: 99%